Physico-Chemical, In Vitro and Ex Vivo Characterization of Meloxicam Potassium-Cyclodextrin Nanospheres - Patrícia Varga; Rita Ambrus; Piroska Szabó-Révész; Dávid Kókai; Katalin Burián; Zsolt Bella; Ferenc Fenyvesi; Csilla Bartos (Pharmaceutics, 2021)
Nasal drug delivery has many beneficial properties, such as avoiding the first pass metabolism and rapid onset of action. However, the limited residence time on the mucosa and limited absorption of certain molecules make the use of various excipients necessary to achieve high bioavailability. The application of mucoadhesive polymers can increase the contact time with the nasal mucosa, and permeation enhancers can enhance the absorption of the drug. We aimed to produce nanoparticles containing meloxicam potassium (MEL-P) by spray drying intended for nasal application. Various cyclodextrins (hydroxypropyl-β-cyclodextrin, α-cyclodextrin) and biocompatible polymers (hyaluronic acid, poly(vinylalcohol)) were used as excipients to increase the permeation of the drug and to prepare mucoadhesive products. Physico-chemical, in vitro and ex vivo biopharmaceutical characterization of the formulations were performed. As a result of spray drying, mucoadhesive nanospheres (average particle size <1 µm) were prepared which contained amorphous MEL-P. Cyclodextrin-MEL-P complexes were formed and the applied excipients increased the in vitro and ex vivo permeability of MEL-P. The highest amount of MEL-P permeated from the α-cyclodextrin-based poly(vinylalcohol)-containing samples in vitro (209 μg/cm2) and ex vivo (1.47 μg/mm2) as well. After further optimization, the resulting formulations may be promising for eliciting a rapid analgesic effect through the nasal route.